Anisotropic MoS2 Nanosheets Grown on Self‐Organized Nanopatterned Substrates. Issue 19 (10th March 2017) - Martella, Christian; Mennucci, Carlo; Cinquanta, Eugenio; Lamperti, Alessio; Cappelluti, Emmanuele; Buatier de Mongeot, Francesco; Molle, Alessandro
Abstract : Manipulating the anisotropy in 2D nanosheets is a promising way to tune or trigger functional properties at the nanoscale. Here, a novel approach is presented to introduce a one‐directional anisotropy in MoS2 nanosheets via chemical vapor deposition (CVD) onto rippled patterns prepared on ion‐sputtered SiO2 /Si substrates. The optoelectronic properties of MoS2 are dramatically affected by the rippled MoS2 morphology both at the macro‐ and the nanoscale. In particular, strongly anisotropic phonon modes are observed depending on the polarization orientation with respect to the ripple axis. Moreover, the rippled morphology induces localization of strain and charge doping at the nanoscale, thus causing substantial redshifts of the phonon mode frequencies and a topography‐dependent modulation of the MoS2 workfunction, respectively. This study paves the way to a controllable tuning of the anisotropy via substrate pattern engineering in CVD‐grown 2D nanosheets. Abstract : Manipulating the anisotropy in 2D nanosheets is a promising way to tune or trigger functional properties at the nanoscale. Here, a novel approach is presented to introduce a one‐directional anisotropy in MoS2 nanosheets via chemical vapor deposition onto rippled patterns. This study paves the way to a controllable tuning of the anisotropy via substrate pattern engineering.